Activity-based costing methodology as tool for costing in hematopathology laboratory - Gujral Sumeet; Dongre Kanchan; Bhindare Sonal; Subramanian P; Narayan HKV; Mahajan Asim; Batura Rekha; Hingnekar Chitra; Chabbria Meenu; Nair C (Wolters Kluwer Medknow Publications, 2010)
Background: Cost analysis in laboratories represents a necessary phase in their scientific progression. Aim: To calculate indirect cost and thus total cost per sample of various tests at Hematopathology laboratory (HPL) Settings and Design: Activity-based costing (ABC) method is used to calculate per cost test of the hematopathology laboratory. Material and Methods: Information is collected from registers, purchase orders, annual maintenance contracts (AMCs), payrolls, account books, hospital bills and registers along with informal interviews with hospital staff. Results: Cost per test decreases as total number of samples increases. Maximum annual expense at the HPL is on reagents and consumables followed by manpower. Cost per test is higher for specialized tests which interpret morphological or flow data and are done by a pathologist. Conclusions: Despite several limitations and assumptions, this was an attempt to understand how the resources are consumed in a large size government-run laboratory. The rate structure needs to be revised for most of the tests, mainly for complete blood counts (CBC), bone marrow examination, coagulation tests and Immunophenotyping. This costing exercise is laboratory specific and each laboratory needs to do its own costing. Such an exercise may help a laboratory redesign its costing structure or at least understand the economics involved in the laboratory management.